Phenotypic and Genomic Detection of Salmonella spp. in Broiler Chicken Meat Across Distribution Chains in Surabaya, Indonesia - Caterina Hidayati; Isnawati; Wahyu Setyarini; Radita Yuniar Arizandy (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to investigate Salmonella spp. contamination in broiler chicken meat obtained from traditional markets, modern markets, and poultry slaughterhouses in Surabaya, East Java, using phenotypic and genomic approaches. A total of 15 broiler chicken meat samples were analyzed. Phenotypic identification was performed through colony morphology observation, Gram staining, and biochemical testing, while genomic confirmation was conducted using Polymerase Chain Reaction (PCR) targeting the invA gene. The results showed that two samples (13.33%) obtained from traditional markets were positive for Salmonella spp., whereas all samples collected from modern markets and poultry slaughterhouses tested negative. These findings indicate variation in contamination levels among different distribution sources, with a higher risk of Salmonella spp. contamination in broiler chicken meat sold in traditional markets. Therefore, strengthened surveillance and improved hygiene and sanitation practices are essential to ensure food safety and protect public health. This study provides comparative evidence of Salmonella spp. contamination across different broiler chicken distribution channels through the integration of phenotypic identification and molecular confirmation.